Kewenangan Dokter Puskesmas dalam Visum et Repertum sebagai Bukti dalam Pengadilan Kasus Tindakan Kekerasan Seksual - Sabrina Nuraini Sari; Nella Septyani Suade (CV Rewang Rencang, 2025)
This study addresses the complex issue of sexual violence against women and children as a public health and legal concern, highlighting the crucial role of Visum et Repertum (VeR) as evidence. Challenges arise regarding the authority of Puskesmas (Community Health Center) doctors in issuing VeR and its validity in court, often due to limited medicolegal understanding in primary healthcare facilities. Through a literature review, this normative legal research analyzes the scope of Puskesmas doctors' authority in preparing VeR for sexual violence cases and evaluates its legal validity as admissible evidence. The findings indicate that VeR issued by Puskesmas doctors is valid and recognized by judges, supported by legal regulations and judicial practice. Nevertheless, standardization and capacity building for Puskesmas doctors are essential to optimize VeR's effectiveness as evidence.